A low pressure gravity-driven membrane filtration (GDM) system for rainwater recycling: Flux stabilization and removal performance. (April 2017) - Ding, An; Wang, Jinlong; Lin, Dachao; Tang, Xiaobin; Cheng, Xiaoxiang; Wang, Hui; Bai, Langming; Li, Guibai; Liang, Heng
Abstract: Rainwater is a nature resource, which can be widely used for non-potable and potable applications in water scared countries after appropriate treatment. Gravity-driven membrane filtration (GDM) process is a promising technology for decentralized rainwater treatment due to no backwashing, flushing and chemical cleaning. In this study, we established a single lab-scale GDM system for the stored rainwater (simulative cellar rainwater) treatment with two months operation, and a stored tap water was used as a compared system to evaluate the permeability and organics removal performance. Results showed that GDM exhibited a good performance for bacteria and turbidity removals, but the removal performance of DOC was undesirable due to the low rejection of low molecular-weight fulvic. Additionally, the permeate flux reached stable with the value of 6–6.5 L/m 2 h during 60 days operation in the rainwater system, however, the tap water system stabilized only at 4 L/m 2 h. Hydraulically reversible resistance accounted for large proportions (90%) of the total resistance, which indicated that the flux could be recovered by simple physical flushing. The bio-fouling layer adhered on the membrane surface was characterized at the end of the filtration experiment. Higher bio-activity with lower EPS (polysaccharides and proteins) contents of the fouling layer were found in the rainwater system compared with the control system, which was the main reason for the higher flux. These results show that rainwater can be treated in a single GDM process with low maintenance, which makes the process suitable for decentralized water supply. Highlights: Rainwater was recycled by low pressure gravity-driven membrane system. Flux stabilized at 6–6.5 L/m 2 h during two-month operation. The activity of the bio-fouling layer played important roles for the stabilization. The fouling resistance was dominated by the reversible bio-fouling layer.